209 Prognostic factors related to recurrence and survival of early stage vulvar squamous cell carcinoma. (4th December 2020) - Wang, Yun; Lindemann, Kristina; Bruheim, Kjersti; Barrameda, Anne; Davidson, Ben; Skeie-Jensen, Tone
Abstract : Introduction/Background: In patients treated for clinical early stage vulvar squamous cell carcinoma (VSCC), recurrence rate is reported to be up to 37%. Identification of prognostic factors related to recurrence and survival will help to tailor surgical treatment and follow-up with the aim to prevent recurrence and prolong survival. The aim of the study is to evaluate prognostic factors for recurrence and survival among patients with early stage VSCC. Methodology: This is a retrospective study of patients with early stage VSCC who were treated at Oslo University Hospital – Radium hospital between 01.01.2006 and 31.12.2016. Clinicopathological characteristics, treatment and follow-up were extracted from the medical records. Univariate analysis and multivariate logistic regression and Cox proportional hazard regression analysis were used to identify prognostic factors for recurrence, time to recurrence (TTR) and overall survival (OS). A p-value of <0.05 was considered to be statistically significant. Results: 133 patients with clinical stage I VSCC were included. All patients underwent primary vulva surgery and evaluation of groin lymph node status. The median age was 64 years (range 29–93 years), and groin lymph node metastases were identified in 22.6% of patients. The median follow-up time was 67 months (range 5–165). The 5-year recurrence and survival rates were 23.3% (31 of 133) and 72.2% (96 of 133), respectively. In multivariate analysis, the presence of lichen sclerosus and groin lymph node metastasis were independent significant prognostic factors for recurrence and TTR, with an odds ratio (OR) (95% CI) of 5.37 (2.13–13.53) and 2.8 (1.17–6.72), respectively, for recurrence, and a HR (95% CI) of 2.6 (1.35–5.19) and 2.2 (1.13–4.26) for TTR, respectively. Age >70 years and a history of recurrence were independent prognostic factors for OS, with an HR (95% CI) of 3.0 (1.58–5.65) and 2.1 (1.57–6.15), respectively. Pathological tumor-free margin distance was not an independent prognostic factor for recurrence, TTR or OS, neither using a cutoff of 8 millimeters, nor as a continuous variable. Conclusion: Patients with lichen sclerosus and groin lymph node metastasis have a higher risk for recurrence and shorter TTR. Patients with age >70 years and a history of recurrence have significantly poorer OS. Pathological tumor-free margin distance was not an independent prognostic factor for recurrence and survival. Disclosures: All authors declare no conflict of interest.